Behindert das (deutsche) Recht die zeithistorische Forschung? - Jan Thiessen (Rechtsgeschichte - Legal History)
Contemporary History is history that is »still smoking« (Barbara Tuchman). Since there is no smoke without ﬁre, contemporary historical research deals with historical eras or events that continue to be widely discussed due to political controversies persisting up to the present day. Moreover, contemporary historical research is subject to numerous legal restrictions. This is particularly true for contemporary legal history. Academic freedom and freedom of information have to be weighed against personality rights and judicial independence. In that light, the article reviews essential provisions of German law regarding the legal access to historical sources, especially the Federal Archives Act, and illustrates practical issues in writing contemporary legal history.